Estimation of plowing forces on vehicles driving through deep snow. (December 2022) - Welling, Orian; Shoop, Sally; Letcher, Ted; Elder, Bruce; Bodie, Mark
Highlights: Empirical measurements of vehicle snow-plow force match closely to proposed physics-based model. Proposed physics-based model for snow plowing forces developed zones of snow compression, shear, and turbulence as the vehicle travels through snowpack. At low vehicle speeds, the force of compressing snow dominates inertial forces of accelerating snow in front of the vehicle. Abstract: Determining trafficability of winter surfaces is a critical capability for Army operations in cold regions. Over the years, a substantial amount of research has been conducted to characterize different winter surfaces (and different vehicles, tires, and tracks on these surfaces) for this purpose. Trafficability model for snow and ice have been implemented in numerous tools currently in use by the Army including the NATO Reference Mobility Model (NRMM), GeoWATCH, and other stand-alone implementations. However, these models are generally based on empirical testing of vehicles driving through snow of shallow to moderate depth and do not adequately capture additional compressive and inertial plowing forces as well as friction drag forces resulting from deep snow being pushed forward by the vehicle bumper, nose, compression caused by the undercarriage, or undercarriage components catching the snow (e.g. suspension arms). In this paper we propose a generalizable snow plowing model for estimating the force required for a vehicle to travel through deep snow. The results of the model compare well to empirical measurements of the force required for a mid-weight all-terrain tactical vehicle to move through different depths of deep snow (over the bumper) and at different ride height settings.